2022
DOI: 10.1037/ocp0000310
|View full text |Cite
|
Sign up to set email alerts
|

When the medium massages perceptions: Personal (vs. public) displays of information reduce crowding perceptions and outsider mistreatment of frontline staff.

Abstract: Crowded waiting areas are volatile environments, where seemingly ordinary people often get frustrated and mistreat frontline staff. Given that crowding is an exogenous factor in many industries (e.g., retail, healthcare), we suggest an intervention that can “massage” outsiders’ perceptions of crowding and reduce the mistreatment of frontline staff. We theorize that providing information for outsiders to read while they wait on a personal medium (e.g., a leaflet, a smartphone) reduces their crowding perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Another intervention approach looked at structural changes to reduce aggression in highly crowded places, perhaps timely during a viral pandemic where fears of crowding are high. Reyt et al (2022) assessed objective crowding in waiting rooms of health This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Interventions To Reduce Interpersonal Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Another intervention approach looked at structural changes to reduce aggression in highly crowded places, perhaps timely during a viral pandemic where fears of crowding are high. Reyt et al (2022) assessed objective crowding in waiting rooms of health This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Interventions To Reduce Interpersonal Stressmentioning
confidence: 99%
“…Another intervention approach looked at structural changes to reduce aggression in highly crowded places, perhaps timely during a viral pandemic where fears of crowding are high. Reyt et al (2022) assessed objective crowding in waiting rooms of health care facilities in Study 1 and with manipulated stimuli in a coffee shop in Study 2, manipulating perceptions of crowding by how communication was conveyed. They found that modes that orient people to their personal space (i.e., a handheld pamphlet or cell phone) mitigates the aggressive response to objective crowding compared to modes that orient people to others around them (i.e., a public sign or poster).…”
Section: Interventions To Reduce Interpersonal Stressmentioning
confidence: 99%